Requerimentos e concessões fundiárias: experiências sociais de apropriação do solo urbano (Santa Maria, Rio Grande do Sul, século XIX) - Becker Neto, Octávio (Universidade do Vale do Rio dos Sinos, 2020)
The present research aims to identify how social relations influenced the urban space conformation of Vila de Santa Maria da Boca do Monte, in the Province of Rio Grande do Sul, in the second half of the 19th century, until mid-1870s. Through the City Council’s minutes, more specifically the land requisitions registered in this documentation, it is sought to locate individuals acting in the context of urban land distribution. The acknowledgment of a significant German social contingent asking for and receiving land highlights an ethnic issue, which is observed first from the City Council perspective, and then from the Germans themselves. The concessions made by the local legislature and the consequent clash with the Province lead to a discussion about 19th century Brazilian land law, from which it is sought to understand the position of two different public power instances about urban land. In this sense, it is established a dialogue with broader themes, of regional and national impact, such as the insertion and integration of German immigrants in the 19th century, and the Brazilian land restructuring after the Lei de Terras law, from 1850. Methodologically, this work is inspired by Italian social microhistory, privileging the observation of behaviors and social relationships given in a circumscribed space. The sources used, especially the City Council’s minutes, postmortem inventories and matrimonial records, point at ethnic and parental background criteria that support and condition such relationships and behaviors. By the exam of these performances and practices developed by the agents in the context of land appropriation, it becomes evident the influence of the articulation of a collectivity on Santa Maria’s urban space conformation and occupation.
Keywords: Espaço urbano; Requerimentos de terra; Apropriação fundiária; Relações sociais; Santa Maria; Urban space; Land requisitions; Land appropriation; Social relations; ACCNPQ::Ciências Humanas::História